KEMAMPUAN SOSIALISASI DAN GERAK MANIPULATIF BERBASIS KELOMPOK PADA ANAK USIA 4-5 TAHU - Mohamad Syarif Sumantri; Tjia Endrawati (Jurnal Ilmiah Visi, 2013)
The purpose of this study is to answer the problem of how to improve the social skills of children aged 4-5 years through group -based manipulative motion activity. The research was carried out in the children group of 4-5 years old at The Kindergarten of IPEKA Sunter, North Jakarta as from March through May 2011. The research method used an action research approach through cycles: initial assessment planning, action, observation and reflection, the research carried out in 2 cycles, data collected by the instrument type observation, interviews and documents,with mixmethod data analysis, and data validity by triangulation methods and sources. The results of data analysis show an overall group -based manipulative movement has increased the social skills of children aged 4-5 years was 76.77 % , makes no difference that drives the improvement of learning outcomes is through manipulative motion activity -based group has given children the opportunity to interact intensively, fun atmosphere, providing the freedom of choice of activity , active child, role sharing, collaboration, and empathy. The implication of this study is if the activity group -based manipulative movement properly made and programmed it will have a positive impact on the development potential of the socialization of children.